Case Study: Liquidity analysis through Financial Ratios - Rengasamy, Dhanuskodi; Ya’u, Abba; Olaniyi, Oladokun Nafiu (2022)
This case study, "Liquidity Analysis of Sherwin-Williams Company," is about a top-ranked paint company around the globe. The analysis is based on data extracted from the company's annual report for the year 2021. This study covers the details of Brand Finance (BF) and its ranking activities. Additionally, it provides sufficient information about liquidity ratios and their classification. This case study helps to analyse the liquidity performance of Sherwin-Williams Company through financial ratio analysis. This case study helps students and the reader community understand the liquidity position of the case company. Furthermore, the methodology allows them to perform similar analyses on other businesses. The case is developed to attain certain objectives: to understand the financial ratios for measuring the liquidity of the company, to analyse and interpret the liquidity position of the company, and to conclude the liquidity position of the company based on the financial ratios.